OPEN GOVERNMENT STUDIES: A BIBLIOMETRIC ANALYSIS - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
The aim of this research is to analyze open government research bibliometrics. This research uses a qualitative approach with bibliometric analysis methods. The data used in this research is of secondary type, originating from the Scopus database. Data was collected using the Publish or Perish application using the keyword